Encrypted/connected paths: Jesuit heritage between Rio de Janeiro and São Paulo - Martins, Renata Maria De Almeida (Estudos Avançados, 2021)
This study discusses the paths of destruction, dispersion, reconstruction and preservation that marked the history of the Jesuit heritage in the southeastern region of Brazil, particularly the old colleges of Rio de Janeiro and São Paulo, and the missions on the coast of São Paulo and Rio de Janeiro, in the context of global / local / connected histories. The study of these cases highlights general characteristics common to other areas of Brazil and Hispanic America, given the global circulation of models, books, artists and objects, and also points out problematic elements that affect and hinder our current knowledge of this type of colonial production.